Family Counseling on Parenting in The Prevention of Adolescent Bullying Behavior: A Literature Review - Saputra, Rizky Lukman; Susanto, Tantut; Rasni, Hanny; Kurdi, Fahruddin (Al-Hijrah Indonesia, 2024)
Background: Bullying is aggressive behavior that often occurs among teenagers. Bullying has negative consequences such as threatened well-being and mental health that puts its victims at risk of committing suicide. A total of 37,381 child abuse cases occurred during 2011-2018 in Indonesia. Family dynamics and relationships reflected through parental parenting have not shown significant changes in the character building of the younger generation. Purpose: The purpose of this study is to describe family counseling about parenting in the prevention of adolescent bullying behavior. Methods: There are 11 articles sorted from 5 electronic journal databases: ScienceDirect, PubMed, Springerlink, ProQuest, and Google Scholar. The following combination of search terms is